2011
DOI: 10.5582/ddt.2011.v5.5.202
|View full text |Cite
|
Sign up to set email alerts
|

Targeting apoptosis pathways in cancer with magnolol and honokiol, bioactive constituents of the bark of <i>Magnolia officinalis </i>

Abstract: Magnolol and honokiol, main active compounds from the bark of Magnolia officinalis, have been found to have various pharmacological actions, including anti-oxidative, anti-inflammatory, anti-tumor, and anti-microbial properties, without appreciable toxicity. Recently, the anti-tumor activity of magnolol and honokiol has been extensively investigated. Magnolol and honokiol were found to possess anti-tumor activity by targeting the apoptosis pathways, which have been considered as targets for cancer therapies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 85 publications
(96 reference statements)
1
26
0
Order By: Relevance
“…Numerous signaling pathways have been implicated in the regulation of apoptosis by magnolol [27]. Magnolol triggers the release of Bid, Bax and cytochrome c from mitochondria, and induces apoptosis via a caspase-independent pathway in non-small cell lung cancer cells [7].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous signaling pathways have been implicated in the regulation of apoptosis by magnolol [27]. Magnolol triggers the release of Bid, Bax and cytochrome c from mitochondria, and induces apoptosis via a caspase-independent pathway in non-small cell lung cancer cells [7].…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol is an important bioactive compound present in Magnolia bark extracts, which has been used as a folk remedy for centuries in China, South Korea, and Japan to treat gastrointestinal disorders, cough, anxiety, stroke, and allergic diseases (4). Honokiol has been reported to have a variety of broad mechanisms of action, such as anti-inflammatory activity (5, 6), along with antiangiogenic (7) and cardio-beneficiating (8, 9), and neuro-protective activity (10, 11), without appreciable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that honokiol possesses wide-ranging biological and clinically relevant properties, without an appreciable degree of toxicity5. Several studies have reported that honokiol induces cell-cycle arrest and apoptosis in cancer cells67 and inhibits tumor-associated lymphangiogenesis and metastasis in lung carcinoma models induced by vascular endothelial growth factor8. Zhang et al 9.…”
mentioning
confidence: 99%